Strategi Koping Keluarga yang Terdampak Covid-19 di Nagari Surian: Studi Kualitatif - Bunga Islami Yusa (Ranah Research : Journal of Multidisciplinary Research and Development, 2021)
COVID-19 is a positive single-strain RNA virus that infects the respiratory tract. The diagnosis starts from the general symptoms of fever, cough, and difficulty breathing. Identified that COVID-19 can be a stressor for families so families need effective coping strategies to deal with stressors that have an impact on psychological conditions. The study aimed to identify coping strategies implemented by families affected by COVID-19 in Nagari Surian. This study used a qualitative method with data collection using interviews and observation and analyzed descriptively. There were four participants in this study from different families affected by COVID-19. The results of the study show that the coping strategies used by families affected by COVID-19 in Nagari Surian are different. One subject uses emotional-focused coping to overcome problems and the other three subjects use a mixed coping strategy, namely problem-emotional-focused coping to overcome the problems they face.